PENERAPAN DATA MINING PEMASARAN PRODUK MENGGUNAKAN METODE CLUSTERING - Melladia Melladia; Dian Eka Putra; Leila Muhelni (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2022)
This study aims to build a data mining application that is able to classify products marketed by companies to find out the products needed for the following month. This application groups non-hierarchical data which is designed to divide existing data into two or more groups so that the same data can be entered into other groups. In this study, the data used is data from PT Cipta Niaga Semesta Mayora Group and the method used is clustering. Data mining is computer-based data processing to gain knowledge. By using data mining, processing sales data at PT Cipta Niaga Semesta Mayora Group becomes easier and gains useful knowledge to take steps to face competition. For this reason, the company's management foresight is needed in choosing technology to help work so that the costs incurred are proportional to the company's opinion. The development of this framework is completed through several stages starting with the first data collection, followed by the second stage of application design, the third stage of the four stages of program development and program implementation. Using data mining applications can help PT Cipta Niaga Semesta categorize the products it sells so that the company can predict the product inventory needed for the following month. So with the new information the company can find out what products customers want.